1996
DOI: 10.1046/j.1365-3083.1996.d01-300.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity Inhibition of Cytolytic Lymphocytes by Omeprazole

Abstract: This study examined the in vitro effect of omeprazole (OM) on various types of murine cytocidal lymphocytes. The results show that OM caused a strong inhibition of basal natural killer (NK) activity in spleen cells (SC) from untreated CD2F1 mice; in peritoneal exudate cells and SC activated in vivo by injection of maleic anhydride divinyl ether 1,2-copolymer (MVE-2) or inactivated Candida albicans (CA); in lymphokine-activated killer (LAK) activity generated in vitro from splenocytes cultured with rhIL-2 and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 42 publications
0
20
0
3
Order By: Relevance
“…52 Third, in vitro studies have shown that acid-suppressive drugs may impair the function of neutrophils and the activity of natural killer cells. [53][54][55][56][57][58][59] Interestingly, the most striking increase in the risk of pneumonia in association with proton pump inhibitors was observed in the first week of use. The risk of pneumonia in association with use of proton pump inhibitors was attenuated, but still significant, between 30 and 180 days.…”
Section: Main Findingsmentioning
confidence: 99%
“…52 Third, in vitro studies have shown that acid-suppressive drugs may impair the function of neutrophils and the activity of natural killer cells. [53][54][55][56][57][58][59] Interestingly, the most striking increase in the risk of pneumonia in association with proton pump inhibitors was observed in the first week of use. The risk of pneumonia in association with use of proton pump inhibitors was attenuated, but still significant, between 30 and 180 days.…”
Section: Main Findingsmentioning
confidence: 99%
“…3,9,10,12 PPI-induced agranulocytosis and impaired lymphocyte functions have recently been reported. 11,17 The neutrophils that infiltrate gastric mucosa are affected by PPIs. PPIs can attenuate neutrophil adherence to endothelial cells by inhibiting the expression of adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
“…8 The first PPI, omeprazole, has been proven to attenuate neutrophil and lymphocyte functions in vitro. [9][10][11][12] PPIs affect the interaction of neutrophils with endothelial cells and attenuate neutrophil association with chemostatic cytokines of gastric mucosa. 2,4,13 However, the effect of PPIs on gastric mucosa and neutrophils has not been thoroughly clarified.…”
mentioning
confidence: 99%
“…In contrast, ranitidine enhances NK cell activity and increases Th1:Th2 ratio. [56][57][58][59] A prospective, randomized study of abdominal surgery patients found that ranitidine diminished the postoperative reduction in spontaneous and stimulated NK cell activity but did not significantly change the Th1:Th2 ratio or mononuclear cell responses. 57 …”
Section: Proton Pump Inhibitors/h2 Receptor Antagonistsmentioning
confidence: 99%
“…En revanche, la ranitidine favorise l'activité des cellules NK et augmente le rapport Th1/Th2. [56][57][58][59] Une étude randomisée prospective portant sur des patients subissant une chirurgie abdominale a trouvé que la ranitidine réduisait la diminution postopératoire de l'activité des cellules NK, spontanée et stimulée, mais qu'elle ne modifiait pas de façon significative le rapport Th1/Th2 ou les réponses des cellules mononucléaires. 57 Agonistes des récepteurs adrénergiques alpha-2…”
Section: Inhibiteurs De La Pompe à Protons/antagonistes Du Récepteur H2unclassified